Os encontros entre missionários e indigenas: nas Cartas do Pe. José de Anchieta - Santos, Jandevaldo Felipe dos (2017)
This dissertation is focused on studies of contact zones and the cultural meetings between native Brazilian people and Jesuits missionaries in Portuguese America, dated by sixteenth century. For noticing the stress and conflicts, we choose analyses some letters written by priest Jose de Anchietain reference to the missionary activities in the cities of Sao Vicente and Piratininga (1554 1570). Based on an interdisciplinary premise, in cooperation with Anthropology and History references about the theme, the proposal of our analysis is identifying references in the missionary letters which allow us to think how native Brazilian people were instructed about religion and how they resisted to the new culture that they were being forced to, as well as the challenges and possible contradictions shown in the Colonizer’s praxis. We intend, this way, contribute to the knowledge expansion about the introduction of the Catholicism in Brazil by sixteenth century, in the context of Science of Religion